THE CONTRIBUTION OF PRINCIPAL SUPERVISION AND MOTIVATION FOR TEACHER ACHIEVEMENT TO THE MORALE IN PAHANDUT SUB-DISTRICT - Lili Aulia Sari; Anik Anik (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
Abstract: Based on the brief description, several problems were formulated in this study as follows: (1) whether there is a contribution of the principal's supervision to the morale of PAUD teachers in Pahandut District, Palangkaraya City (2) whether there is a contribution of teacher achievement motivation to the morale of PAUD teachers in Pahandut District, Palangkaraya City (3) whether the contribution of jointly supervising the principal and motivating the teacher's achievement to the morale of PAUD teachers in Pahandut District, Palangkaraya City. The method used is a descriptive method, which is to describe the contribution of the principal's supervision and motivation for achievement to the morale of PAUD teachers in Pahandut District, Palangkaraya City. The study population was PAUD teachers in Pahandut Subdistrict, Palangkaraya City as many as 233 teachers, using proportional random sampling techniques obtained a sample of 139 teachers. Data collection techniques for principal supervision variables (X 1), teacher achievement motivation variables (X 2) and teacher morale variables (Y) using questionnaires in the form of a Likert scale. Instrument testing uses data validation and reliability tests, while data analysis requirements testing uses normality tests, linearity tests, multicholinearity tests and heteroskedasticity tests. To determine the contribution of the principal supervision variable, the teacher achievement motivation variable to the teacher's morale in this study was carried out using regression and multiple regression tests using the SPSS 17.0 program application.Keywords: Principal Supervision, Teacher Achievement Motivation, Teacher Morale